Day 2 Tue, August 02, 2022 2022
DOI: 10.2118/211996-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Curvature Assessment of Some Natural Surfactants for Chemical Enhanced Oil Recovery Applications in Nigeria

Abstract: Chemical enhanced oil recovery (CEOR) application of natural surfactants is based on potential interfacial tension (IFT) alterability and eco-friendly considerations. The reduced IFT is associated with microemulsion formation in relation to a surfactant’s characteristic curvature. Lately, surface activities of natural surfactants have gained interest in Nigerian laboratory studies with no attention given to their hydrophilicity/hydrophobicity. This research focuses on molecular weight determination, micelle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The density of the oil sample is 0.890 g/cm 3 measured using DMA 45; the molecular weight is 252 g/mol, which was determined using the freezing point depression method, and the dead crude oil sample has an acidity of 3.7 mg KOH/g. The procedures of each test are explained elsewhere. The SARA test was also performed, and the results are presented in Table ; details of how the test is usually done can be found in the literature …”
Section: Methodsmentioning
confidence: 99%
“…The density of the oil sample is 0.890 g/cm 3 measured using DMA 45; the molecular weight is 252 g/mol, which was determined using the freezing point depression method, and the dead crude oil sample has an acidity of 3.7 mg KOH/g. The procedures of each test are explained elsewhere. The SARA test was also performed, and the results are presented in Table ; details of how the test is usually done can be found in the literature …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a positive Cc value means that the surfactant tends to form water-swollen in an oil phase (W/O microemulsion) . The Cc value of conventional carboxylate surfactant is reported to be + 0.97 (Antonio, 2015). According to Table 4.6, the results showed that all carboxylate based extended surfactants had more negative Cc values than the conventional carboxylate surfactant.…”
Section: Hld Calculationmentioning
confidence: 96%